Structural Health Monitoring Sensor based on A Flexible Microstrip Patch Antenna - Hamse Abdillahi Haji Omer; Saidatul Norlyana Azemi; Azremi Abdullah Al-Hadi; Ping Jack Soh; Mohd Faizal Jamlos (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
A microstrip patch antenna strain sensor operating at dual frequencies 1.8GHz and 2.4GHz have been designed based on the relation between the resonant frequency and the strain applied to it. Felt substrate with a height of 3mm and dielectric constant of 1.44 and shield conductor are used for the design of this antenna. Testing results show that the resonant frequency of the microstrip patch antenna is 1.78 GHz and 2.4 GHz, which agrees with the simulation. The resonant frequency of the microstrip patch antenna increases linearly with the increase of the applied strain. This microstrip patch antenna strain sensor can be integrated with other components easily and have a great potential applications in structural health monitoring systems.